Invertebrate Biomass and Richness in Various Food Plot Types in East Texas - Charles W. Anderson; R. Montague Whiting Jr.; Donald R. Dietz; Richard M. Capps (National Quail Symposium Proceedings, 2017)
As northern bobwhite (Colinus virginianus) chicks are dependent on invertebrates for food, land managers often use spring/summer food plots to meet these needs. We examined invertebrate production in native vegetation and 6 different food plot types (i.e., fallow disking only; fallow disking and fertilizing; or disking, fertilizing, and planting a single species [browntop millet, iron and clay peas, or sorghum] or a multi-species mix [browntop millet, catjang peas, iron and clay peas, Japanese millet, and pearl millet]) in the Pineywoods of east Texas. Invertebrates were collected weekly during the summers of 1997 and 1999 and for 5 weekly sampling periods during summer, 1998. For each food plot type, invertebrates were separated from debris, air dried, and weighed as a group. Bi-weekly, a 100-invertebrate sub-sample was randomly selected from each sample and sorted to order with weight and number of individuals recorded. When spring precipitation was sufficient, multi-species food plots produced greater (P < 0.05) invertebrate biomass than fallow or native vegetation plots, and all cultivated plots had more (P < 0.05) biomass than native vegetation. Likewise, all cultivated plots had more (P < 0.05) biomass than fallow plots in early summer but not in mid- and late summer. A combination of multi-species (with legumes) food plots and fallow disking should provide bobwhite chicks with invertebrates throughout most summers.
Keywords: Colinus virginianus; east Texas; food plots; invertebrate biomass; invertebrate richness; northern bobwhite